2022
DOI: 10.22159/ajpcr.2022.v15i10.45583
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Adverse Drug Reactions on Cardiovascular Drugs in Hospitalized Patients of a Tertiary Care Hospital – A Prospective Analysis

Abstract: Objective: The present study was taken up to assess the adverse drug reactions (ADRs) based on the spontaneous reactions among the inpatients who were hospitalized for the treatment of cardiac ailments. Methods: A prospective and observational study was done in the department of cardiology for a period of 6 months. Patients on cardiac drug therapy were evaluated to detect unwanted effects and were given treatment for the developed complications. The ADRs were identified, followed up, and documented. Results: I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
2
0
0
Order By: Relevance
“…Skin reactions accounted for 14.54% of cases, followed by the Central Nervous System (CNS) at 10.9%. These findings are consistent with the literature study 20 , where the GI system (37%), skin (25%), and CNS (12%) were the most commonly affected systems. Another study also reported a high incidence of GI ADRs (42.1%), followed by skin and subcutaneous tissue (33.8%) 24 .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Skin reactions accounted for 14.54% of cases, followed by the Central Nervous System (CNS) at 10.9%. These findings are consistent with the literature study 20 , where the GI system (37%), skin (25%), and CNS (12%) were the most commonly affected systems. Another study also reported a high incidence of GI ADRs (42.1%), followed by skin and subcutaneous tissue (33.8%) 24 .…”
Section: Resultssupporting
confidence: 93%
“…In our study, we observed an incidence of adverse drug reactions (ADRs) at a rate of 2.75%, constituting a significant portion, specifically 47.01%, of the total DRPs. This trend aligns with findings from two other studies, where they reported similar ADR incidences of 2.17% 19 and 1.82%, respectively 20,21 . There was an another study reported a lower incidence of 3.7% ADRs among hospitalized patients in India, highlighting the need to investigate the reasons for this discrepancy, including under-reporting and inadequate pharmacovigilance systems 22 .…”
Section: Resultssupporting
confidence: 92%